Online self-representation of Malaysian Muslim female students: a Facebook case study - Noumeur, Meriem Narimane; Idid, Syed Arabi (Department of Media Studies, Faculty of Arts & Social Sciences, University of Malaya, 2019)
Social networking websites play an important role in our lives. These websites provide several services that allow users to enjoy their time in cyberspace by providing them with space to represent their personalities in the virtual world. Using Goffman’s dramaturgical theory, this study aims to identify the way Malaysian women represent themselves, by depicting and managing their virtual identities through Facebook while exploring the way they construct their identities and realize their online presence. A total of 133 female students from a Malaysian university were involved in the study on their self-representations (online and offline); highlighting the way they presented their identities online and suggesting whether their offline influenced the virtual identities. The findings showed a significant effect of the offline feelings on online self-representation and revealed a strong relationship between offline and online presence. It indicated the difficulty of separation between virtual and real identity.